Some is not everything? Designing an instrument that measures the clinical learning environment holistically - Hugo-van Dyk, Lizemari; Jordaan, Hanlie (International Journal of Practice-based Learning in Health and Social Care, 2024)
This article describes the development as well as face and content validation of an instrument for measuring the clinical learning environment of professional healthcare students. A methodological research design was used to develop the instrument and a Delphi technique was used to determine face and content validity. The research was conducted systematically in two phases to construct the instrument, and to establish face and content validity. Phase 1 comprised a general literature overview to identify existing instruments. The retrieved instruments were thematically analysed into the four themes of atmosphere, teamwork, workload and learning opportunities, and then the first version instrument was drafted. In Phase 2, the first version instrument was evaluated for face and content validity. Thirty-six healthcare professional experts responded in the consensus Delphi study, and consensus was reached after three rounds. A consensus Delphi study confirmed the face and content validity of 62 items. The second version of the new instrument was determined. A new holistic clinical learning environment measuring instrument, based on existing instruments, was developed to promote quality student placements.